Transformations of microdefect structure in silicon crystals under the influence of weak magnetic field - Vladimirova, T.P.; Kyslovs’kyy, Ye.M.; Molodkin, V.B.; Olikhovskii, S.I.; Koplak, O.V.; Kochelab, E.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Quantitative characterization of complex microdefect structures in annealed
silicon crystals (1150 °С, 40 h) and their transformations after exposing for one day in a
weak magnetic field (1 T) has been performed by analyzing the rocking curves, which
have been measured by a high-resolution double-crystal X-ray diffractometer. Based on
the characterization results, which have been obtained by using the formulas of the
dynamical theory of X-ray diffraction by imperfect crystals with randomly distributed
microdefects of several types, the concentrations and average sizes of oxygen precipitates
and dislocation loops after imposing the magnetic field and their dependences on time
after its removing have been determined.